DETERMINATION OF UREA-HUMIC ACID DOSAGE OF VERTISOLS ON THE GROWTH AND PRODUCTION OF RICE - Retno Suntari; Rurini Retnowati; Soemarno Soemarno; Mochammad Munir (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
The main problem of the use of N fertilizer in paddy soil Vertisols is the low efficiency. Urea-humic acid applications at certain dosage are believed to increase rice growth and production. This study was aimed to examine the effect of urea and urea-humic acid to the amount and form of N-available, N uptake, plant growth, and the production of rice. Five dosage levels of urea-humic acid were applied for rice on Vertisols. Results of the research showed that the urea-humic acid fertilizer could increase the content of N-NH4+ soil at 28 days and N-NO3- soil at 42 days. The urea-humic acid could improve plant height, number of tillers, and total dry weight. The highest rice production is achieved by 100% humic acid-urea, especially on parameters of dry weight effectively harvested and effectively milled, with 5.56 tons and 4.61 tons per hectare respectively. Correlation between soil N-NO3- level with soil N-NH4+ level was significant at p = 0.05 (r = 0.871). Efficiency of urea-humic acid fertilizer at 100% recommended dosage (200 kg urea-humic acid) to the dry weight of effectively harvested crop with dry weight of effectively milled crop was 22% compared to the recommended urea fertilizer (200 kg ha-1).